The struggle for the influence in Central Asia between PRC, USA and RF - Arzikulov, A. A.; Aigarayeva, A. A. (Journal of Oriental Studies, 2016)
The purpose of this article is to examine and analyze the political struggle between the USA, RF and the PRC in the Central Asia region. It deals with the main interests and methods of influence of these countries in CA. Transformation of political key points is observed in the article.